INTEGRASI FILSAFAT HUMANISTIK DALAM MANAJEMEN BISNIS DAN KEUANGAN BERKELANJUTAN: STUDI KEPUSTAKAAN - yusni, Nurtasyani; Syahrani, Anugrah; Rahayu, Andi Aprilia; Karyono, Otong (MBISKU: Jurnal Manajemen Bisnis dan Keuangan, 2026)
This study aims to analyze the integration of humanistic philosophy in sustainable business management and finance through a literature review. Although ESG is increasingly becoming a strategic paradigm in modern corporate practice, the study results show that its implementation is often instrumental and not yet rooted in moral values, potentially resulting in superficial sustainability. Through an analysis of academic literature, it was found that humanistic values ​​such as human dignity, justice, empathy, and moral responsibility have a significant contribution to strengthening organizational performance, governance quality, and consistency of ESG implementation. A key finding of this study is the theoretical and empirical gap in the lack of explicit integration of humanistic values ​​within the framework of ESG, CSR, GHRM, and sustainable finance, especially in developing countries. This study concludes that authentic sustainability requires an ethical foundation derived from humanistic philosophy and recommends the development of a more humane and long-term theoretical framework and governance practices.